Cover Feature: Thermodynamic Programming of Erbium(III) Coordination Complexes for Dual Visible/Near‐Infrared Luminescence (Chem. Eur. J. 50/2018). Issue 50 (21st August 2018) - Golesorkhi, Bahman; Guénée, Laure; Nozary, Homayoun; Fürstenberg, Alexandre; Suffren, Yan; Eliseeva, Svetlana V.; Petoud, Stéphane; Hauser, Andreas; Piguet, Claude
Abstract : Molecular erbium complexes are on the dark side of luminescence, with usually no emitted visible light. Upon systematic tuning of the peripheral ligands, a rare metal‐centered green fluorescence can be implemented, which paves the way for lanthanide‐based molecular upconversion. More information can be found in the Full Paper by S. Petoud, A. Hauser, C. Piguet et al. onpage 13158 .